2017
DOI: 10.13189/aeb.2017.050804
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Effect of Financial Development on Economic Growth after the 2008 Global Financial Crisis

Abstract: A growing body of theoretical and empirical literature analyses the relationship between finance and economic growth. The relationship has been strongly supported by many empirical analyses. However, the 2008 Global Financial Crisis (GFC) and the significantly improved econometric techniques made scholars to revisit this relationship. The main motivation of this paper is to empirically revisit the relationship between financial development and economic growth, especially one under the effect of the world's gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…Particularly, Girgin et al [97], having analysed 147 countries during 2000-2013, confirmed a decline in both the mutual correlation of economic growth and financial development, as well as a deterioration in the representativeness of some standard indicators of economic development in models. Notwithstanding the relationship between financial development and economic growth remains significant, the ratio of M2 to GDP has a negative effect on economic growth.…”
Section: Financial Depth-economic Growth Nexus During Gfcmentioning
confidence: 95%
“…Particularly, Girgin et al [97], having analysed 147 countries during 2000-2013, confirmed a decline in both the mutual correlation of economic growth and financial development, as well as a deterioration in the representativeness of some standard indicators of economic development in models. Notwithstanding the relationship between financial development and economic growth remains significant, the ratio of M2 to GDP has a negative effect on economic growth.…”
Section: Financial Depth-economic Growth Nexus During Gfcmentioning
confidence: 95%
“…In contrast, the study by Liming (2014) found that labour force participation rates are insufficient to support economic growth in a sample of 284 Chinese prefecture cities. In addition, others have found a negative and insignificant relationship between the workforce and economic growth (Girgin, Nguyen & Karlis, 2017).…”
Section: Long-run Effect Of Determinants Of Economic Growth Andmentioning
confidence: 99%
“…Some critiques can be made about the empirical analysis that runs between 2001 and 2012. During the given time frame, the bulk shipping industry had peak level in vessel prices both in newbuilding and second-hand market and had peak level in freight rates; and right after 2008 Global Financial Crisis (GFC), had a very sharp decrease in all the markets and the economy (Celik Girgin et al 2017). This might have led to have empirical outputs against conventional approach in the shipping industry since GFC had distorted the market and the freight rate could not reflect the real demand status, or even, in turn, the freight rate volatility could be determined by the instant second-hand vessel transaction price volatility.…”
Section: Dry Bulk Shipping Marketmentioning
confidence: 99%